(untitled) (Journal of Nepal Geological Society, 2013)
Morphometric analysis of a watershed provides a quantitative description of the drainage system which is an important aspect of characterization of watershed. The analysis requires measurement of linear features, aerial aspects, gradient of channel network and contributing ground slopes of the drainage basin. The morphometric characteristics at the watershed-scale may contain important information regarding its formation and development because all hydrologic and geomorphic processes occur within the watershed. In this study morphometric property of the Bagmati River Basin (BRB) was investigated using different morphometric attributes and hypsometric analysis in order to investigate geomorphic development of the river basin, in an active tectonic zone. DEM has been prepared from the contour and spot height data using digital topographic maps of 1:25000-scale acquired from the Department of Survey, Nepal. The main stem Bagmati River is the eighth order perennial river that stretches for 206 km with an elongated catchment of area 3761 sq. km. It consists of 39 sub-basins of fourth order and higher. The study shows that the drainage system of the BRB is attaining a mature stage from a youth stage from lower order streams to the higher order streams in geomorphic development process. Some exceptions occurred at higher order stream segments, where drainage development seems to control by structure and lithology. According to the analytical results, erosional stage and level of tectonic activity of sub-basins differ from each other. Generally, the lithology and geological structure seems to control the drainage texture and relief of the BRB. The river system within the Kathmandu Valley is attaining maturity having meandering channels with wide flood plains, whereas rivers of the Lesser Himalaya and the Siwaliks are at youth stage with erosional potential. The downstream part of higher order stream segments are in mature stage having potential for lateral erosion and meander migration. Therefore, the Bagmati River stretch, especially the eight order one poses vulnerability to bank erosion.